The Study of Ahmad Jam’s Verbal Thoughts - Olimov, Karomatullo (2021)
Ahmad Jami is a well-known mystical figure, and his mystical roots are often discussed. But there has been no independent research into his verbal thoughts yet. An important question that has been discussed in this regard is what elements and components of Ahmad Jam's verbal thoughts contain? The present article is a descriptive-analytical one and uses the library method to investigate the mentioned question. The results of the study indicate that wisdom, Genesis, Step, Judgment, and magnitude, the vision of God at the resurrection is one of the most important theological components of Ahmad Jam. The results of this study indicate that the influence of theological issues in Ahmad Jam's thought is so much that his works without knowledge of his theological views will be incomplete.